2015
DOI: 10.1021/acsnano.5b03355
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Controlled Synthesis of Isotopic Yttrium-90-Labeled Rare Earth Fluoride Nanocrystals for Multimodal Imaging

Abstract: Isotopically labeled nanomaterials have recently attracted much attention in biomedical research, environmental health studies, and clinical medicine because radioactive probes allow the elucidation of in vitro and in vivo cellular transport mechanisms, as well as the unambiguous distribution and localization of nanomaterials in vivo. In addition, nanocrystal-based inorganic materials have a unique capability of customizing size, shape, and composition; with the potential to be designed as multimodal imaging p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 75 publications
(146 reference statements)
0
35
0
3
Order By: Relevance
“…Infrared light, comprising 43% of the solar spectrum, appears to be an appealing energy source for photocatalysis as well. In recent years, up‐conversion materials, usually encountered in biological and clinical studies, have attracted considerable attention by photocatalytic researchers 57. Rare‐earth‐element‐doped upconversion materials absorb infrared light and emit UV and visible light via a two‐ or multi‐photon mechanism, which has been well‐documented 58.…”
Section: Discussionmentioning
confidence: 99%
“…Infrared light, comprising 43% of the solar spectrum, appears to be an appealing energy source for photocatalysis as well. In recent years, up‐conversion materials, usually encountered in biological and clinical studies, have attracted considerable attention by photocatalytic researchers 57. Rare‐earth‐element‐doped upconversion materials absorb infrared light and emit UV and visible light via a two‐ or multi‐photon mechanism, which has been well‐documented 58.…”
Section: Discussionmentioning
confidence: 99%
“…One potential downside of this approach is the possibility of crystalline mismatch if the radioactive element greatly differs from the element that makes up the rest of the particle’s lattice, resulting in radionuclide detachment. Examples of radiodoped lattices are rare-earth fluorine nanocrystals 48 as well as gold 49 , iron oxide 40 and copper nanoparticles 50 . Avoiding issues of crystalline mismatch, fluorescent gold nanoparticles have been doped with 198 Au, allowing both nuclear and optical imaging with the same nanoparticle 51 .…”
Section: Nanoparticles and CL In Life Sciencesmentioning
confidence: 99%
“…[3] Following these seminal studies,awide range of beta-, [42,60] positron-, [15, 17b,59, 61] and alpha-emitting [62] isotopes have been used for imaging based on Cerenkov radiation. Fore xample,P aik et al [54] made use of the excellent efficiency of 90 Yi ns timulating Cerenkov luminescence when designing and exploring 90 Ydoped RENPs by combined it with ap aramagnetic gadolinium host for multimodal imaging applications.The ability to use 90 Y-doped nanomaterials for optical imaging was evaluated through in vitro studies,w hich indicated ag ood correlation between total radiance and radioactivity. [54] As ac onsequence of its ability to bridge nuclear and optical imaging techniques,CRcould potentially support the translation of already approved radiotracers for optical imaging.…”
Section: Imaging and Therapeutic Applicationsmentioning
confidence: 99%
“…Fore xample,P aik et al [54] made use of the excellent efficiency of 90 Yi ns timulating Cerenkov luminescence when designing and exploring 90 Ydoped RENPs by combined it with ap aramagnetic gadolinium host for multimodal imaging applications.The ability to use 90 Y-doped nanomaterials for optical imaging was evaluated through in vitro studies,w hich indicated ag ood correlation between total radiance and radioactivity. [54] As ac onsequence of its ability to bridge nuclear and optical imaging techniques,CRcould potentially support the translation of already approved radiotracers for optical imaging. [63] Even though the amount of light generated from CR emitters is still lower than that of bioluminescence and fluorescence,t he nondependencyo na nexternal light source is known to reduce tissue autofluorescence and can result in significantly improved signal-to-background ratios.…”
Section: Imaging and Therapeutic Applicationsmentioning
confidence: 99%